2004
DOI: 10.1093/ndt/gfh650
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of furosemide vs hydrochlorothiazide in patients with chronic renal failure and hypertension

Abstract: Hydrochlorothiazide increased the fractional excretion of sodium and chloride more than furosemide did in hypertensive severe renal failure patients. Mean arterial blood pressure decreased by the same amount with both diuretics. Combining furosemide and hydrochlorothiazide did not increase the efficacy of hydrochlorothiazide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 9 publications
1
48
0
1
Order By: Relevance
“…18 While thiazide therapy is considered generally ineffective when the GFR is <20 to 30 cc ⁄ min, 4,19 at least one randomized controlled study showed no difference in antihypertensive efficacy comparing HCTZ 25 mg with long-acting furosemide 60 mg in patients with stage 4 or 5 chronic kidney disease. 16 Probably the dose of furosemide was too low in this trial of 7 patients with GFRs ranging from 12 cc ⁄ min to 41 cc⁄ min. Therefore, there is fair evidence, based on the unanimous conclusions of six small prospective randomized trials, to recommend HCTZ 50 mg or chlorthalidone 25 mg rather than furosemide to treat resistant hypertension when the GFR is >50 cc ⁄ min due to improved efficacy (Table I).…”
mentioning
confidence: 79%
“…18 While thiazide therapy is considered generally ineffective when the GFR is <20 to 30 cc ⁄ min, 4,19 at least one randomized controlled study showed no difference in antihypertensive efficacy comparing HCTZ 25 mg with long-acting furosemide 60 mg in patients with stage 4 or 5 chronic kidney disease. 16 Probably the dose of furosemide was too low in this trial of 7 patients with GFRs ranging from 12 cc ⁄ min to 41 cc⁄ min. Therefore, there is fair evidence, based on the unanimous conclusions of six small prospective randomized trials, to recommend HCTZ 50 mg or chlorthalidone 25 mg rather than furosemide to treat resistant hypertension when the GFR is >50 cc ⁄ min due to improved efficacy (Table I).…”
mentioning
confidence: 79%
“…Importantly, 5 randomized controlled trials (RCT) reported between 1979 and 2012 have investigated thiazide efficacy in CKD [30][31][32][33][34], also detailed in Table 1. The earliest was a double blind crossover study that enrolled 16 woman with mean creatinine clearance of 14 mL/min/1.73 m 2 who were treated with chlorothiazide 500 mg twice daily or placebo for 6 weeks before crossover [30].…”
Section: Older Studies Of Thiazides In Ckdmentioning
confidence: 99%
“…After washout they then crossed over to the other drug. Finally, they received 30 day period of combination therapy [33]. The second RCT was reported in 2012 and enrolled 23 subjects with measured GFR of 25 mL/min [34].…”
Section: Older Studies Of Thiazides In Ckdmentioning
confidence: 99%
“…Drug-induced diuresis is beneficial in many life threatening disease conditions such as cardiac failure, chronic and moderate cardiac insufficiencies, acute edema of the lung, nephritic edema syndrome, arterial hypertension, diseases related with the retention of fluids etc 1,2 . Ural syrup is a patent and proprietary Ayurvedic formulation which contains extract of Tribulus terrestris (Gokshur) 3 , Berginia ligulata (Pashanbhed) 4 , Boerhaavia diffusa (Punarnava) 5 , Crataeva nurvala (Varun) 6 , Raphanus sativus (Mulika) 7 , Dolichos biflorus (Kulathi) 8 , Smilax china (Chopchini) 9 and powder of Sodii carbonas (Swarjikakshar) 10 , Borax (Shuddha Tankan) 11 , Potasii carbonas (Yavakshar) 12 , Kala namak (Black Salt) 13 and Citrus acida (Nimbuk) 14 .…”
Section: Introductionmentioning
confidence: 99%